Perubahan Dinamika Islam: Dari Keemasan Abad Pertengahan ke Tantangan Zaman Modern di Timur Tengah" - Ahmad Sahhil Fuady; Eva Siti Faridah (Almustofa Journal of Islamic Studies and Research, 2025)
Islam is a religion brought by the Prophet Muhammad SAW whose contents teach his people about Faith in Allah SWT must have a history from his childhood to adulthood and even to old age because he is a human role model for the whole world whose life can be used as a guide in guiding his people starting from the way he preached to bring Islam, to whom his teachings were delivered, was it only young children who he conveyed his teachings? The young, the old!, whether his teachings were only delivered to people who were rich? The poor! whether his teachings were delivered to people who had white skin? while the brown to the black! However, he taught, delivered his teachings to anyone regardless of race, ethnicity, throne and whatever, when did he deliver his teachings, was it only once a week, once a month, or once a year? However, he spreads, teaches Islam every day both by word, deed, silence, even with his traits, why he was sent to be a Messenger, are we not worthy! Of course we as humans will not be able to be like him because he was chosen directly by Allah as rahmatan lil alamin, where he da'wah, whether only in one place or two places,Of course not he taught this religion everywhere until what we see now is also thanks to him and to how he interacted with people who opposed his teachings, how he cultivated himself to remain calm when his da'wah was rejected even when he went to Thoif his teachings were rejected then the angels were willing to turn the mountain to fall on the Thoifites but he replied with: “If they knew I was a prophet, they would not oppose me.” Then he raised his hand, ‘O Allah, make this place and this people a place for people of faith.’ What a noble prophet and the teachings he brought, namely Islam, because with history we can find out what really happened.